Features of calcium metabolism and the severity of clinical manifestations of osteochondrosis of the lumbosacral spine in men and women - Platonova, E. I.; Nasibullin, B. A. (Journal of Education, Health and Sport, 2017)
The authors based on a comparative analysis of the severity of structural and neurological manifestations in patients with osteochondrosis of the lumbosacral spine revealed a relationship between calcium metabolism disorders and catabolic processes in the frequency of calcification of the discs, spinal cord and ossiflicate vertebral bodies. The authors also showed a unidirectionality of these changes in men and women with their greater severity in the former. In addition, the authors showed that in men, these changes are more significant in younger people, and in women, the relationship of changes with age is not expressed.